EFFECTS OF CONFLICT MANAGEMENT STRATEGIES ON ORGANIZATIONAL PERFORMANCE OF PUBLIC TECHNICALAND VOCATIONAL EDUCATION AND TRAINING INSTITUTIONS IN MAKUENI COUNTY, KENYA - JESSY NGINA KITUSA (Machakos University Press, 2025)
This study examined how conflict management strategies affect the organizational performance of public Technical and Vocational Education and Training (TVET) institutions in Makueni County, Kenya. The objective of the study was to investigate the effects of conflict management strategies (collaboration strategy, accommodation strategy, compromising strategy, and avoidance strategy) on organizational performance of public TVET Institutions. Using a mixed-methods approach with a convergent parallel design, the research combined quantitative data from structured questionnaires with qualitative insights from semi-structured interviews. The target population of the study was 328 participants, comprising of principals, trainers, support staff, and final-year students from David Mbiti Wambuli Technical and Vocational College and Kibwezi West Technical and Vocational College. A sample size of 181 was determined by the formula of Yamane by the use of simple, census and purposive. random sampling techniques. The reliability of the questionnaire was established. The Alpha of 0.0.812, which shows high consistency of data. Quantitative analysis, the analyses using Z-scores, Chi-Square, T-tests and multiple linear regression indicated a. poor statistical significance (R 2 = 0.067, p = 0.762) between conflict management tactics (collaboration, accommodation, compromise and avoidance) and performance of the organization, in terms of pass rates in external examination and student. enrollment trends. The most prevalent was found to be collaboration as presented in the qualitative results. strategy (46% of references), then compromise (31%), accommodation (15%), and avoidance (7%), which means that win-win approaches are preferred as proactive. A major factor that affected occurrence of conflicts was resource constraints. resolution effectiveness. The results are in line with available literature that highlights. The incorporation of collaboration in facilitating innovation and stakeholder involvement, albeit local. The influences included such factors as resource shortages and institutional policies. This research is a response to a gap, concentrating on TVET institutions and presenting evidence to. support policy-makers and educational administrators to manage conflict better. organizational performance and practices.